Secured SO a for Interoperable e-Learning Platforms Based on Encryption Algorithms - Vijaya lakshmi, G; Dinesh kumar, G; V.Sai Lohith, M; Akhil Reddy, Y (International Journal of Engineering and Technology, 2018)
The Lionization of distance education is cake walking on day basis and is the most tendered process to obtain the information in any field. Compared to the traditional education it is providing many facilities in various aspects. As the improvements are rapid in this area, the requirements are also cake walking. A Service Oriented Architecture addresses issue by designing the views of reference architecture from the contents of various domains. It personalizes the delivery of e-content based on knowledge and preference of the learner. As the information provided in the e-learning systems is to be made secure along with the user information a specific security system is to be designed by using the concepts of system security. For this various algorithms such as Triple DES, RSA, AES are taken in to consideration as an experimental analysis. Only the authorized person can utilize the content without interfered by the other user. By the analysis experimentally AES is showing highest accuracy among all the algorithms.Â Â